ANALISIS PENGEMBANGAN WISATA LUAK GADANG BUKIK BAKA UNTUK MENINGKATKAN DAYA TARIK WISATA DI KABUPATEN AGAM, SUMATERA BARAT - Vina Kumala; Dewi Anggraini (Ensiklopedia Social Review, 2020)
Luak Gadang Bukik Baka is a natural tourist attraction located in Agam Regency, West Sumatra. This tourist attraction is relatively new, so it is still managed by the community. An attraction that is favored by this tourist attraction is a fish pond with a karst cliff on one side. Bukik Baka is a beautiful hill that has lovely sees and can also be used as a camping site. This tourist attraction is still in the early stages of growth. Since opening in April 2018, the available tourist facilities are still minimal, but tourist visits to this tourist attraction are very busy. This study aims to figure out how to develop the tourism potential of Luak Gadang Bukik Baka, so that it can attract tourist visits to Jorong Guguak Rangpisang, Nagari Kamang Hilia, Agam Regency. The research approach used is the qualitative descriptive method. Obtaining the informant's researchers used the snowball technique. Observation, question, and answer (interview), and recording were used as data collection techniques. Based on the findings of the study, it can be inferred that the current innovations are in the areas of activities and services, such as lodging and facilities. Meanwhile, Luak Gadang Bukik Baka has not fully evolved in terms of physical aspects, beauty, accessibility, socio-economic, and cultural aspects. It is hoped that the Agam Regency Government will continue to support the Jorong Guguak Rangpisang community in developing the Luak Gadang Bukik Baka into a popular tourist destination.